Graphene-Coated Activated Carbon Fiber Cloth Positive Electrodes for Aluminum Rechargeable Batteries with a Chloroaluminate Room-Temperature Ionic Liquid. Issue 12 (1st January 2017) - Tsuda, Tetsuya; Uemura, Yuya; Chen, Chih-Yao; Hashimoto, Yu; Kokubo, Itsuki; Sutani, Kouichi; Muramatsu, Kazuo; Kuwabata, Susumu
Abstract : Functional carbon materials have recently attracted attention as positive electrode active materials for Al rechargeable batteries in conjunction with an Al negative electrode and a chloroaluminate ionic liquid electrolyte. This study explores a new carbon material, a graphene-decorated activated carbon fiber cloth (ACFC), for the positive electrode. Graphene-decorated ACFCs can be used in a binder-free manner and will directly contribute to increased gravimetric capacity of the whole electrode [mAh (gelectrode ) −1, not per the active material]. Specifically, the positive electrode behaviors of three types of ACFC-based electrodes are examined in a Lewis acidic AlCl3 −1-ethyl-3-methylimidazolioum chloride ([C2 mim]Cl) room-temperature ionic liquid. Uncoated and low-loading graphene-coated ACFC electrodes show an electric double layer capacitor (EDLC)-like behavior, whereas the intercalation/deintercalation reaction of chloroaluminate anion (e.g., [AlCl4 ] − ) is observed for the high-loading graphene-coated one. These electrodes exhibit a good cyclability and satisfactory coulombic efficiency up to 800 cycles at a current density of 500 mA g −1 .